Pepper Spot ("Gomasho") on Napa Cabbage - David Studstill; Eric Simonne; Jeff Brecht; Phyllis Gilreath (EDIS)
HS-1101, a 5-page illustrated fact sheet by David Studstill, Eric Simonne, Jeff Brecht, and Phyllis Gilreath, describes this physiological problem affecting the midribs of Napa cabbage, the symptoms, possible internal causes and postharvest handling effects on pepper spot. Includes selected references and a table showing sensitivity by variety. Published by the UF Department of Horticultural Sciences, May 2007.